2021
DOI: 10.3390/plants10010074
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Application of Foliar Salicylic Acid and Propolis Enhances Antioxidant Defenses and Growth Parameters in Tomato Plants

Abstract: Salicylic acid (SA) and propolis (PR) are known to regulate the physiological process and to have a relevant role in bioactive compounds content. Our experiment was designed to evaluate the effect of SA and PR application on the growth, yield, and quality parameters of tomato grown for the fresh market in field conditions in Egypt. We studied the effect of twelve treatments where SA (0.50, 1.00, 1.50, 2.00, and 2.50 mM) and PR (1, 2, 10, 20, and 100 mg propolis mL−1) were applied at increasing doses as a sole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…This activity is mainly attributed to the phenolic components' redox properties and chemical structures that can neutralize the reactive oxygen species [38]. Previous studies also showed that the combination of SA with other elicitors as propolis in small concentrations may enhance the antioxidant capacity of some crops like tomato [39]. The major identified phenolic in the UPLC-ESI-MS/MS profiles, 3,4-dicaffeoylquinic acid (Table 2, Figure 1), was reported to have strong antioxidant activity [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…This activity is mainly attributed to the phenolic components' redox properties and chemical structures that can neutralize the reactive oxygen species [38]. Previous studies also showed that the combination of SA with other elicitors as propolis in small concentrations may enhance the antioxidant capacity of some crops like tomato [39]. The major identified phenolic in the UPLC-ESI-MS/MS profiles, 3,4-dicaffeoylquinic acid (Table 2, Figure 1), was reported to have strong antioxidant activity [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…So, +SA-seed can induce characteristics that are beneficial during water restriction conditions allowing the maintenance of a larger photosynthetic area and allocation of resources to the roots that assist in the absorption of water and nutrients (Jangid and Dwivedi 2017). A large number of works have indicated that SA enhances growth attributes -leaf area and dry matter production -in tomato when exposed to water stress (El-Hady et al 2021;Galviz-Fajardo et al 2020;Gharbi et al 2018;Lobato et al 2021). Effects on root growth must be carefully considered, Abbasi et al (2020) highlight that SA improved and kept the root system of cucumber plants, improving the absorption of nutrients, increasing the carbohydrate content of flowers and fruits, all this resulting in the increased number and size of fruits.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies report that SA has the ability to induce drought tolerance by increasing antioxidant activity (El-Hady et al 2021;Hayat et al 2008;Lobato et al 2021), many others also point out that it is not a general response (Bortolin et al 2020;El-Esawi et al 2017). Furthermore, Saruhan et al (2012) reported that this is a SA-induced mechanism of water stress tolerance, consequence of the ability of SA molecule to bind to CAT and to inhibit its activity while intensifying SOD activity (Razmi et al 2017;Galviz-Fajardo et al 2020) and finally results in enhanced H 2 O 2 levels as the ones observed in leaves and roots with +SA-seed.…”
Section: Discussionmentioning
confidence: 99%
“…Propolis has been used as a herbal medicine and several useful activities have been described for propolis, including antiviral, antibacterial, antifungal, anti-inflammatory, antioxidant and the protection of plants against abiotic stress [ 1 , 2 , 3 ]. However, the location of the plant, bee species, seasonality, climatic differences and solvent extraction processes can affect the chemical composition and biological properties [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%